IoT-Enabled Forecasting of Vehicle Based Carbon Emissions and Smart Fuel Management: Optimizing Efficiency and Performance - Kale, Rashmi B.; Shaikh, Nuzhat Faiz (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The implementation of an IoT-based device in the vehicle for capturing, notifying, monitoring and analyzing the real time data of the vehicles through gas, dust density sensors and notifications through mobile application. Sensor generated data transfer to electronic sensor data processing microcontroller ESP-32 into human readable values through cloud on Mobile application or Web Based application. Captured data through sensors successfully demonstrates the objective based methodology and framework to measure the individual vehicle carbon emission. Notification displays on Mobile application through IoT device sensors to monitor and manage fuel consumption effectively, predicting usage patterns, optimizing routes, and suggesting fuel-saving measures based on real-time data analysis